Biomimetic optimization of silicone breast implant integration: insights into wound healing and the foreign body response - Dzobo, Kevin; Wilgus, Traci A.; Mora, Vanessa Zamora; Zoncsich, Audry; de Mezerville, Roberto; Khumalo, Nonhlanhla; Bayat, Ardeshir (Frontiers in Bioengineering and Biotechnology, 2025)
Breast augmentation is the most prevalent aesthetic surgical procedure worldwide. While silicone breast implants have evolved in terms of safety and biocompatibility, they inevitably trigger a foreign body response (FBR). This complex process can lead to fibrous encapsulation, capsular contracture, and other complications, often necessitating invasive revision surgeries. This review comprehensively analyzes the molecular and cellular mechanisms underlying FBR, emphasizing the crucial role of implant surface properties. We demonstrate how these properties, including topography, hydrophobicity, and charge, govern the initial protein adsorption patterns, effectively establishing a “molecular fingerprint” that dictates subsequent cellular interactions. This, in turn, orchestrates immune cell activation, notably macrophages, which exhibit plasticity in their polarization into pro-inflammatory (M1) and pro-fibrotic (M2) phenotypes. The balance between these phenotypes influences the extent of fibrosis and capsular contracture. We explored the five distinct phases of FBR: protein adsorption, acute inflammation, chronic inflammation, foreign body giant cell (FBGC) formation, and encapsulation. The impact of implant surface properties on each phase was elucidated, highlighting the dynamic interplay between macrophages, lymphocytes, and matrix. The phenomenon of “frustrated phagocytosis,” where macrophages fail to engulf the implant, leading to FBGC formation and chronic inflammation, is also examined. Finally, we explore promising strategies to modulate FBR and enhance implant biocompatibility, including biomimetic coatings, the use of decellularized matrices, and therapies aimed at disrupting specific molecular pathways involved in fibrosis. This review provides insights into the development of next-generation implants that can harmoniously integrate with the body, minimizing FBR and ensuring long-term clinical success.